Large Eddy Simulation of a Swirl-Stabilized Pilot Combustor from Conventional to Flameless Mode - Ehsan Fooladgar; C. K. Chan (Journal of Combustion)
This paper investigates flame and flow structure of a swirl-stabilized pilot combustor in conventional, high temperature, and flameless modes by means of a partially stirred reactor combustion model to provide a better insight into designing lean premixed combustion devices with preheating system. Finite rate chemistry combustion model with one step tuned mechanism and large eddy simulation is used to numerically simulate six cases in these modes. Results show that moving towards high temperature mode by increasing the preheating level, the combustor is prone to formation of thermal NOx with higher risks of flashback. In addition, the flame becomes shorter and thinner with higher turbulent kinetic energies. On the other hand, towards the flameless mode, leaning the preheated mixture leads to almost thermal NOx-free combustion with lower risk of flashback and thicker and longer flames. Simulations also show qualitative agreements with available experiments, indicating that the current combustion model with one step tuned mechanisms is capable of capturing main features of the turbulent flame in a wide range of mixture temperature and equivalence ratios.